Ligações de Peroba-Rosa (Aspidosperma polyneuron) com cavilhas de eucalipto (Eucalyptus citriodora) - Piedade Jr, Cezar; Stamato , Miguel Carlos; Freire , Wesley Jorge (Revista Ceres, 2025)
The present research was carried out using 316 symmetrical wood testing pieces made of «peroba-rosa» (Aspidosperma polyneuron). The pieces were fastened by using wooden pegs made of Eucaliptus citriodora. The pegs had the usual dimensions.